w-(3-5w)-4=2(w-9)+3

Simple and best practice solution for w-(3-5w)-4=2(w-9)+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for w-(3-5w)-4=2(w-9)+3 equation:



w-(3-5w)-4=2(w-9)+3
We move all terms to the left:
w-(3-5w)-4-(2(w-9)+3)=0
We add all the numbers together, and all the variables
w-(-5w+3)-(2(w-9)+3)-4=0
We get rid of parentheses
w+5w-(2(w-9)+3)-3-4=0
We calculate terms in parentheses: -(2(w-9)+3), so:
2(w-9)+3
We multiply parentheses
2w-18+3
We add all the numbers together, and all the variables
2w-15
Back to the equation:
-(2w-15)
We add all the numbers together, and all the variables
6w-(2w-15)-7=0
We get rid of parentheses
6w-2w+15-7=0
We add all the numbers together, and all the variables
4w+8=0
We move all terms containing w to the left, all other terms to the right
4w=-8
w=-8/4
w=-2

See similar equations:

| -9n-7=-8n | | 5y+(-2y)-7=20 | | -2(8p+3)+3(4p+5)=2+2p+7-7p | | 4(x+3)-4=(1/2x+1) | | 130+5x+5=180 | | -10-8b=-6b+6 | | -2=|q|-9 | | 6-3s=-9 | | 3x−55(x−22)=−6+2x-8 | | 2r+12/8=4r-36/4 | | m+2m-6=12+12m | | 3x−5​(x−2​)=−6+2x8 | | -5(-3n+1)=-95 | | 2/14x=46 | | 4(7x+6)-7(6+4x)=-3x+6x | | -3.3h=-5.1h-18.72 | | 33x-−55​(x−22​)=−66+22x8 | | |j+3|=4 | | Y=2x-60 | | 4r+8/8=5r-10/5 | | 6-7=5x-9x+15 | | X+8-x=-4(-4-6x)-4(6x+2) | | 20-x=35/2x | | 100=900-100n | | 6n-7(1+2n)=5(-2n-3)-2 | | 3x-5(x-2)=6+2x-8 | | 2x=2x-60 | | 0.3a(0.2a-0.5)+0.2(a+2)=1.3 | | 9x+10+3x-16=180 | | 95+55+6x=180 | | 3x+15+5x-23=90 | | a=355-5 |

Equations solver categories